Suicidal behavior of the military officer and its nature, forms and characteristics - Semenov, S. S.; Riutin, V. V. (Honor and Law, 2019)
The suicide as the social-dangerous phenomenon is highlighted. The article is devoted to the analysis of the nature, forms characteristics of the military officer’s person’s suicide behavior with the view of suicide prevention.